2021
DOI: 10.1007/s10072-021-05746-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of cardiovascular autonomic failure in the differential diagnosis of α-synucleinopathies

Abstract: The α-synucleinopathies comprise a group of adult-onset neurodegenerative disorders including Parkinson’s disease (PD), multiple system atrophy (MSA), dementia with Lewy bodies (DLB,) and — as a restricted non-motor form — pure autonomic failure (PAF). Neuropathologically, the α-synucleinopathies are characterized by aggregates of misfolded α-synuclein in the central and peripheral nervous system. Cardiovascular autonomic failure is a common non-motor symptom in people with PD, a key diagnostic criterion in MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Another prioritized recommendation of the Roadmap meeting included the development of clinical, imaging, and other biofluid markers that reliably track disease progression since clinical indices alone are poorly reflective of progression rate [ 24 ]. Ancillary testing includes autonomic function tests [ 25 , 26 ], olfactory testing [ 27 ], 123I-MIBG cardiac scintigraphy [ 28 ], multimodal MRI assessment [ 29 31 ] (see also Kim et al [ 32 ]), and positron emission tomography (PET) imaging of the translocator protein (TSPO) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another prioritized recommendation of the Roadmap meeting included the development of clinical, imaging, and other biofluid markers that reliably track disease progression since clinical indices alone are poorly reflective of progression rate [ 24 ]. Ancillary testing includes autonomic function tests [ 25 , 26 ], olfactory testing [ 27 ], 123I-MIBG cardiac scintigraphy [ 28 ], multimodal MRI assessment [ 29 31 ] (see also Kim et al [ 32 ]), and positron emission tomography (PET) imaging of the translocator protein (TSPO) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation for the association between RBD and HR was the impact of α-synuclein. Previous studies have confirmed that α-synuclein was detectable within the heart and cardiovascular autonomic failure was a common symptom in α-synucleinopathies [ 47 , 48 ]. The α-synuclein in heart may further contributed to myocardial disorders, including cardiomyopathy, septal fibrosis, and ventricular hypertrophy [ 49 ].…”
Section: Discussionmentioning
confidence: 88%
“…Cardiac denervation is rare at the early stages of MSA, a close differential diagnosis of PAF. [ 17 ]…”
Section: P Athophysiology [ F ...mentioning
confidence: 99%